Creating Well-Structured Specifications in MOFLON - Amelunxen, Carsten; Rötschke, Tobias (Electronic Communications of the EASST, 2007)
Considering the growing popularity of model-based development, specifications become more complex. As a consequence, graph-based modeling tools have to take measures to handle this complexity. In this paper, we present the metamodeling environment MOFLON which has been developed on top of the FUJABA Toolsuite during the last few years at our department. We focus one of MOFLON’s strongest advantages, i.e. the realization of the abstraction and modularization features introduced by the recent UML 2.0 Infrastructure specification. The new concept of package merge allows to reuse and refine existing models without modifying the original. Subset and redefinition relationships become useful tools to refine associations due to the automatic propagation mechanism generated by the MOFLON code generator. We show how the user can organize large specifications using these concepts and how they effect graph transformation rules and code generation.